Grounding in English and Arabic news discourse - Khalil, Esam N. (John Benjamins Pub. Co., 2000)
Grounding in English and Arabic News Discourse explores the discourse notion of grounding (viz. the foreground-background structure), and examines it in the various structures that occur in short news texts. A text-level approach to grounding and the differentiation between several core concepts relating to the various textual and non-textual structures, distinguish the book from other approaches in the field. A corpus-based analysis focuses on sentence-initial expressions and examines the grounding-signalling function of several markers in both English and Arabic. The analysis captures constra.
Enlargement of author's thesis (Ph. D)--University of Amsterdam, 1999.
Keywords: English language -- Grammar, Comparative -- Arabic.; Arabic language -- Grammar, Comparative -- English.; English language -- Discourse analysis.; Arabic language -- Discourse analysis.; Journalism -- Language.; Anglais (Langue) -- Grammaire comparée -- Arabe.; Arabe (Langue) -- Grammaire comparée -- Anglais.; Anglais (Langue) -- Analyse du discours.; Arabe (Langue) -- Analyse du discours.; Journalisme -- Langage.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Arabic language -- Discourse analysis; Arabic language -- Grammar, Comparative -- English; English language -- Discourse analysis; English language -- Grammar, Comparative -- Arabic; Journalism -- Language; Nieuws.; Informatiestructuren (linguïstiek); Tekstanalyse.; Engels.; Arabisch.; Proefschriften (vorm)